Synthesis of novel star-shaped molecules based on a 1, 3, 5-triazine core linked to different heterocyclic systems as novel hybrid molecules. Issue 72 (14th December 2020) - Diab, Hadeer M.; Salem, Mostafa E.; Abdelhamid, Ismail A.; Elwahy, Ahmed H. M.
Abstract : The synthesis of novel star-shaped compounds based on an s -triazine core and linked to different heterocycles as new hybrid molecules through Michael and Hantzsch reactions is reported. Abstract : The synthesis of novel star-shaped compounds based on an s -triazine core and linked to hexahydroacridinediones, pyrimido[4, 5- b ]quinolones, 1 H -isoquinolino[2, 1- a ]quinolines, tetrahydro-4 H -chromenes, dihydropyrano[2, 3- c ]pyrazoles, thiazole, or benzothiazole as new hybrid molecules through Michael and Hantzsch reactions is reported. For this purpose, 2, 4, 6-tris(4-formylphenoxy)benzaldehyde was used as a versatile precursor.